'Friends with benefits': how tobacco companies influence sales through the provision of incentives and benefits to retailers. Issue Volume 29:Issue e1(2020) (10th February 2020) - Watts, Christina; Burton, Suzan; Freeman, Becky; Phillips, Fiona; Kennington, Kelly; Scollo, Michelle; Lindorff, Kylie; Egger, Sam
Abstract : Background: In countries banning advertising and display of tobacco at point-of-sale, little is known about tobacco companies' continuing promotion of products through incentives and benefits to retailers. Method: A telephone survey of 4527 randomly selected Australian retailers was conducted in August 2018, and identified 800 current tobacco retailers (response rate: 72.4%) who were asked a series of questions about benefits offered to them by tobacco companies and what retailers agreed to in return. Results: 41.1% of retailers reported being provided with a tobacco cabinet and 38.3% reported having a price list supplied by a tobacco company. One-third (33.3%) reported being offered at least one benefit from a tobacco company for doing something in return. Price discounts were the most frequently reported benefit (19.0%), followed by rebates (8.4%) and gifts (3.0%). Retailers also reported offers of prizes and incentives for increasing sales or demonstrating product knowledge. In return, retailers reported giving companies benefits such as prominence on the price list and/or in the tobacco cabinet and/or influence over the product range and stock levels. Conclusion: Tobacco companies are continuing to market tobacco and influence sales through provision of incentives and benefits to retailers. Laws that ban the supply of benefits to consumers should be extended to also prohibit the provision of benefits to tobacco retailers.